Efficacy and safety of behavioural activation on depression in people with co-occurring non-communicable diseases: systematic review and meta-analysis - Yisma, Engida; Muyambi, Kuda; Walsh, Sandra; Othman, Shwikar; Gray, Richard; Tan, Kuan Liung; Steen, Mary; Jones, Martin (Cambridge University Press, 2025)
Background People with non-communicable diseases (NCDs) have a higher prevalence of comorbid depression than the general population. While previous research has shown that behavioural activation is effective for general depression, its efficacy and safety in treating depression associated with NCDs remains unclear.